La història, creadora de mites - Nemes, Krisztina (Acta Hispanica, 2013)
Literary survival of a catalan miners’town in Aragonia sunk by Franco’s decision under the wavesof the Ebro. The collective memory of its community works as a source of inspiration and of oral historyfor its chronicler, himself too son of the town. Only memory can keep alive the town after its death andthe writer, responsible of collecting and registering it does a brilliant job. The inspired literaryreconstruction of the town is represented as a broken mirror, reflecting more than one aspect of eachperson and event from different angles, thus offering the readers a perfectly authentic though fictionalsource of history, that of a compromised eyewitness.